Risk Factors for Near Miss Incident among Long Distance Bus Drivers in Malaysia - Nik Nor Ronaidi NIK MAHDI; Norsa'adah BACHOK; Norlen MOHAMED; Mohd Nazri SHAFEI (Tehran University of Medical Sciences, 2015)
Background: Road traffic accident is a worldwide public health issue that has its highest impact on low and middle income countries including Malaysia. Many previous studies concerned on the causality of the actual accidents and little attention were given to near miss incidents. Hence, the current study was designed to determine the prevalence and associated factors for near miss incident among long distance bus drivers in Malaysia. Methods: A cross sectional study was conducted among 517 long distance bus drivers. Data were collected using interview-guided translated and validated Pittsburgh Sleep Quality Index and Manchester Driver Behaviour questionnaire. Multiple logistic regression analysis was performed to determine the significant factors for near miss incident among long distance bus drivers in Malaysia. Results: The prevalence of near miss incident among long distance bus drivers was 37.5% (95% CI: 33.5, 41.8). The significant associated factors for near miss incident were younger age group (ORadj : 1.99; 95% CI: 1.32, 3.01), longer distance travelled per day (ORadj : 2.34; 95% CI: 1.52, 3.60), sleep disturbances (ORadj : 1.74; 95% CI: 1.19, 2.54) and errors in driving behaviour (ORadj : 1.31; 95% CI: 1.23, 1.39). Conclusion: Self-reported near miss incidents were relatively high among long distance bus drivers in Malaysia. This issue should be taken seriously and preventive action should consider the significant human factors such as younger age group, errors in driving behaviours, sleep disturbances as well as occupational factors like distance travelled per day.   Keywords: Road traffic accident, Near miss, Bus drivers, Malaysia